Pooh's grand adventure : the search for Christopher Robin - A.A.Milne; McCafferty, Catherine (Danbury, Ct.[ Grolier books, 1997)
Christopher Robin leaves a note for Pooh and friends telling them he has to go to school. In a misunderstanding, they believe he has gone to "skull," and they set off on a grand journey to rescue him